Persepsi Majikan/Pihak Pengurusan Terhadap Jurang Kemahiran Pekerja: Kajian Dalam Industri Pembuatan Makanan Dan Minuman Di Sarawak - Fathin Naqiuah, Binti Mohd Zawawi; Wan Sofiah, Meor Osman (2017)
The Faculty of Cognitive Sciences and Human Development (FCSHD) Final Year Project 2 Presentation has been conducted on 3rd May 2017 at the FCSHD Program Meeting Room.